(untitled) (Rhythmos, 2013)
With advancing age, all organ systems undergo anatomical and functional changes. Vasculature suffers generalized stiffening as a hallmark of this process. Although this phenomenon has been described long ago, only in recent years has the clinical significance of the stiffening of the large arteries been widely understood and its correlation with hypertension, coronary heart disease, stroke, heart failure and atrial fibrillation has been recognized. It has also been accepted that it mediates the vascular effects of diabetes mellitus, atherosclerosis and renal disease. 1-5 The arterial systems consists of two functional components with different structural characteristics: a) the large elastic arteries (aorta, carotid and iliac arteries) which store part of the blood ejected during systole and expel it to the periphery during diastole to provide the tissues with a relatively steady flow through the entire cardiac cycle and b) the muscular arteries (arteries below the axillary and femoral ones) which regulate the vascular tone and hence determine the peripheral resistance. The former have a thick tunica media in which the elastic fibers dominate and form numerous concentric layers. The later possess a tunica media characterized mainly by smooth muscle cells and the elastic component is confined to the thin internal and external elastic laminae. The different mechanical properties of the arterial tree along its course and the varying diameter of the arterial branches, gives rise to the reflected waves which are produced when the pulse wave encounters sites with different impedance. A part of these secondary waves amplifies the forward moving wave and another part moves backward to enhance the pressure of the central aorta. Normally it reaches its target in late systole or early diastole and it contributes to the diastolic flow towards the coronary arteries and the periphery... (excerpt)